Chinese Silk Road and Indonesian Maritime Axis Harmony in The Sovereign Law Perspective (Research, Society and Development, 2019)
This study aimed to know the implication of legal sovereignty in bilateral agreements as the intersection consequences of the political economy interests of the Chinese Silk Road and Maritime Axis of Indonesia. Also aimed to explain other further issues in bilateral relations between Indonesia and China, such as; effort in enorcing legal equality, provisions regulate effort to avoid abuse of power, rules on environmental issues, human rights regulation, also regulations in international matters. This study used descriptive qualitative as the methodology. The results showed that the choice of Chinese companies in the Jakarta-Bandung fast train project was purely an economic consideration, the government seems passive in responding to the surge in the number of foreign workers, especially China, which is not accompanied by the local labor absorption, several ethnic Chinese companies are still indicated to pollute the environment, the Government is still cautious in addressing human rights issues in Uyghur, the government is firm about violating illegal fishing of foreign and independent vessels in the dispute over the South China Sea.